DECISION SUPPORT SYSTEM BASED ON BENEFIT COST RATIO METHOD FOR PROJECT TENDER - Rukmana, Siti Hardiyanti; Muslim, Much Aziz (APTIKOM Publisher, 2017)
The procurement process became one of the important aspects for PT. PLN (Persero) to operate thecompany. One way to meet these needs is through the project tender. The tender process aims to get high-gradematerials with the lowest prices that meet the criteria of efficiency PT. PLN (Persero). In order to simplify thebidding process required a decision support system. The method used in this system is Benefit Cost Ratio (BCR).Input in this application are the documents and the tender offer price from bidders with complete tender documentsthat have been validated by prospective bidders and then selected by the tender committee to make an assessment andvalidation winner. The output of this process is the winner of the tender project based on calculations Benefit CostRatio (BCR). Therefore, the method Benefit Cost Ratio (BCR) can be used as a decision support system to determinethe winner of the project tender.